PENGARUH KOMISARIS INDEPENDEN, LEVERAGE DAN KEPEMILIKAN SAHAM INSTITUTIONAL TERHADAP INTEGRITAS LAPORAN KEUANGAN - Fallah, Naufal; Kurniawan, Elan; Putranto, Panji (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of independent commissioners, leverage, and institutional shareholding on the integrity of financial statements in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. This study uses a quantitative method with multiple linear regression analysis, and the entire data analysis process is carried out using the help of SPSS software version 26. The data used is secondary data taken from the annual financial statements of pharmaceutical companies, with a sample of 33 observations, consisting of 11 companies during 3 years of observation. The results of the study show that the independent commissioner variable does not have a significant effect on the integrity of financial statements, Leverage does not have a significant effect. Meanwhile, institutional stock ownership has been proven to have a positive and significant influence on the integrity of financial statements.